The Effect of Furosemide Dose Administered in the Out-of-hospital Setting on Renal Function Among Patients with Suspected Acute Decompensated Heart Failure. Issue 1 (16th January 2015) - Nieves, L. Celeste; Mehrtens, Gia M.; Pores, Noah; Pickrell, Christie; Tanis, James; Satty, Timothy; Chuang, Michelle; Young, Tina C.; Merlin, Mark A.
Abstract: Background: The most effective dose of prehospital furosemide in acute decompensated heart failure (ADHF) has not yet been identified and concerns of worsening renal function have limited its use. Objective: To assess if administering high-dose furosemide is associated with worsening renal function. Methods: The authors conducted a 2-center chart review for patients who presented via a single Emergency Medical Service (EMS) from June 5, 2009 through May 17, 2013. Inclusion criteria were shortness of breath, primarily coded as ADHF, and the administration of furosemide prior to emergency department (ED) arrival. A total of 331 charts were identified. The primary endpoint was an increase in creatinine (Cr) of more than 0.3 mg/dL from admission to any time during hospital stay. Exploratory endpoints included survival, length-of-stay (LOS), disposition, urine output in the ED, change in BUN/Cr from admission to discharge, and change in Cr from admission to 72 hours and discharge. Results: When treated as a binary variable, there was no association observed between an increase in Cr of more than 0.3 mg/dL and prehospital furosemide dose. Baseline characteristics found to be associated with dose were included in the logistic regression model. Lowering the dose of prehospital furosemide was associated with higher odds of attaining a 0.3 mg/dL increase in Cr (adjusted OR = 1.49 for a 20 mg decrease; P = .019). There was no association found with any of the exploratory endpoints. Conclusions: Patients who received higher doses of furosemide prehospitally were less likely to have an increase of greater than 0.3 mg/dL in Cr during the hospital course. LC Nieves, GM Mehrtens, N Pores, C Pickrell, J Tanis, T Satty, M Chuang, TC Young, MA Merlin .The effect of furosemide dose administered in the out-of-hospital setting on renal function among patients with suspected acute decompensated heart failure . Prehosp Disaster Med .2015 ;30 (1 ):1 -8 .